2008
DOI: 10.1080/08923640802039040
|View full text |Cite
|
Sign up to set email alerts
|

Toward Practical Procedures for Predicting and Promoting Success in Virtual School Students

Abstract: Two lines of research have emerged to study the causes and prevention of student failure in virtual (K-12) schools: studies of learner characteristics and studies of learning environment characteristics. To develop a useful model for predicting failure and promoting success in virtual school environments, a study was designed to measure the relation between a combination of student and environmental factors derived from previous research and successful course completion during one semester at a large (N = 4,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 23 publications
2
39
0
5
Order By: Relevance
“…Roblyer et al used a Likert scale that contained 60 measurable variables for conducting a survey of 2,162 E-learning students. Binary logistic regression analysis of the sample data revealed a relatively strong correlation between demographic attributions (such as age) and learning achievement (such as GPA) and student dropout [20]. Nichols et al made use of ordinal regression for analyzing the data obtained from 187questionnaires returned by distance education students; the results showed that among four sets of attributions (namely computer usage attitudes, learning motivation, perception of satisfaction and previous academic performance), only previous academic performance exhibited a strong correlation with dropout [21].…”
Section: B Empirical Researchmentioning
confidence: 99%
“…Roblyer et al used a Likert scale that contained 60 measurable variables for conducting a survey of 2,162 E-learning students. Binary logistic regression analysis of the sample data revealed a relatively strong correlation between demographic attributions (such as age) and learning achievement (such as GPA) and student dropout [20]. Nichols et al made use of ordinal regression for analyzing the data obtained from 187questionnaires returned by distance education students; the results showed that among four sets of attributions (namely computer usage attitudes, learning motivation, perception of satisfaction and previous academic performance), only previous academic performance exhibited a strong correlation with dropout [21].…”
Section: B Empirical Researchmentioning
confidence: 99%
“…Also, this study shows that the predictive validity of the ELR tool is clearly superior to those tools as [39] with 83%, [34] with 67% and [12] with 79.3 %.…”
Section: Discussionmentioning
confidence: 80%
“…The first group called "Success" includes students who have received a grade of D to A +, and the group "Failed" those withdrew from the class with a grade of "AR" or "AX" (AR: withdrawn without academic penalty, AX: withdrawn with academic penalty) or completed it with a grade of E (failure). The student ranking criterion in both groups was almost similar to that of [12]. The independent variables are the five dimensions of ELR, and we created a dichotomous variable (Group) which takes the value "0" if the student has failed and "1" in the case, this variable represents the dependent variable model.…”
Section: Assessment Of Predictive Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Forcing students to take courses online may set up less intrinsically motivated students for failure. Moreover, before students register for online courses, have them take a type of personality test that can predict their level of success based on their answers to questions probing their learning preferences and styles (Roblyer 1999;Roblyer, Davis, Mills, Marshall, & Pape, 2008). Then, students can be better counseled into online or face-to-face courses based on their academic strengths and weaknesses.…”
Section: Beyond Content Disseminationmentioning
confidence: 99%